DEVELOPING SELF-CONFIDENCE THROUGH SINGING PLAY DOLL GAMES IN GROUP A CHILDREN AT AL HUDA TK, BATUKULIANG UTARA DISTRICT - Mumtaz Alvian; Evy Rachmawati (Renjana Pendidikan Dasar, 2023)
The ability of Self-Confidence in group A TK AL HUDA Kindergarten, Batukuliang Utara District, Central Lombok Regency is still not optimal, this happens when children are asked to come forward just to prepare their friends to line up, children are still shy and sometimes cry. The formulation of the problem in this study was: can playing singing dolls develop social-emotional abilities and self-confidence in children in group A Kindergarten AL HUDA, Batukuliang Utara District, Central Lombok Regency. The subjects of this study were the children of Group A Kindergarten AL HUDA, Batukuliang Utara District, Central Lombok Regency, totaling 19 children using the Kemmis and Taggart Classroom Action Research (CAR). It was carried out using three cycles, with data collection techniques in the form of Weekly and Daily Learning Program Plans, self-confidence assessment sheets and teacher observation sheets. Based on the results of implementing Classroom Action Research, the average percentage of completeness in pre-action self-confidence was 36.8%. Followed by remedial actions cycle I and cycle II. In the first cycle, after applying the singing doll game, the average percentage increased by 47% followed by cycle II and also experienced an increase in percentage by 63%, followed by cycle III. In cycle III the percentage increased by 84% and in cycle III this has exceeded the minimum completeness criteria of 75% and the hypothesis is accepted. Thus it can be concluded that playing singing dolls can develop self-confidence in group A TK AL HUDA children, Batukuliang Utara District, Central Lombok Regency